(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2004)
This paper presents the results of a study aimed at investigating the frequency, effectiveness and the ways in which the training in social skills were used as the main treatment for individuals diagnosed as being in Obsessive Compulsive Disorder (OCD), by using a bibliografic survey. Works published and issued by PsycINFO were selected as data resources. The criteria for the search were: (a) being written in the English language; (b) published in scientific journals; (c) and have as key words “Obsessive Compulsive Neurosis” and “Social Skills Training” (and correlated terms). Eighteen papers were selected, and only ten papers were available in article format. Although the number of researches on OCD had increased recently, only a few number of publications have examinated the social abilities as a relevant factor of treatment for OCD. None of the consulted papers had the objective of evaluating the effects of intervention in social abilities on the OCD cases.